Test study on flow field morphology of high-pressure abrasive water jet and erosion and failure characteristics of coal - Bingbing HE; Qiheng REN; Qingxiang WANG; Fucheng ZHANG; Lingjun MA; Yayou XU; Baofu WANG; Xiaolin SONG (Meikuang Anquan)
In view of the demand for coal mine gas control, this study took a coal sample from a mining area in Inner Mongolia as the research object, and carried out a study on the coal breaking mechanism of quartz sand abrasive jet based on the theory of hydraulic pressure relief and permeability enhancement. By precisely regulating the blending ratio of quartz sand in the pre-mixed abrasive water jet system and using the control variable method, the influence laws of three key parameters, namely jet pressure, impact target distance and nozzle diameter, on the morphological characteristics of the abrasive jet and the evolution of coal body damage were mainly investigated. The results show that: with the extension of the jet injection distance, both the pure water jet and the abrasive jet present the edge atomization diffusion phenomenon, and the edge atomization of the abrasive jet is more intense. When the jet pressure increases, the divergence degree of the outer contour of the jet expands and the divergence occurs earlier. The comparison of erosion efficiency shows that under the working conditions of 5 MPa and 6 MPa, the crushing volume of quartz sand abrasive jet is 4.65 and 7.82 times that of pure water jet respectively, confirming that abrasive blending significantly improves the energy conversion efficiency. When impacted in the near-field, the shape of the crushing pit is deep and narrow. When acted in the far-field, the jet diverges, the impact kinetic energy decays, and the shape of the crushing pit is shallow and wide. The nozzle structure optimization experiment shows that with a nozzle diameter of 3.0 mm, an optimized crushing pit with a depth of 27.67 mm and a diameter of 42 mm is formed, and the crushing volume is increased by 2.36 times compared with the nozzle diameter of 1.5 mm. When the nozzle diameter exceeds 3.5 mm, the abrasive accelerates the phase separation, resulting in a decrease in concentration and a 16.2% attenuation of the crushed volume.